A new leech species of Helobdella (Hirudinea, Glossiphoniidae) from San Carlos de Bariloche, Río Negro, Argentina - Gullo, Bettina Sandra (2009)
A new freshwater leech species Helobdella fantasmae n. sp. is described. This description is based on the examination of 12 specimens collected in Laguna Fantasma, Bariloche (41o 05'S 71o 28'W), during December 2002. Leeches were found attached to submerged plants. They were relaxed with gradual addition of 70% ethanol, fixed in 10% formalin, stored in 70% ethanol and stained with borax carmine. Examination of external morphology, dissections and microphotographs were accomplished with a Leica Wild M3Z stereo microscope aided with an Olympus C-4000 digital camera. H. fantasmae n. sp. differs from other species of the genus by the presence of 1 pair of eyes on somite III, crop without gastric chambers, digitiform caeca and postcaeca., short sperm ducts reaching the back of somite XV, atrium pyriform, short ovisacs reaching somite XIII. This is the first record of leeches from an ephemeral wetland in North Patagonia. This finding expands current knowledge of the biodiversity of Hirudinea in South America, increasing the number of known Helobdella spp. from the Rio Negro province (North Patagonia) to 10 species.